Denial and Demise?: Reforming National Identity in Welsh Culture after Brexit. Issue 5 (2nd November 2018) - Schofield, Emma
Abstract : In 2016 Welsh artist Iwan Bala launched a controversial exhibition entitled 'Dyma Gariad, fel y Moroedd' (Here is a Love, Deep as Oceans), in which he depicted a series of startling maps and caricatures about Brexit, from the perspective of a Welsh Remain voter. The collection, which included distorted maps of the United Kingdom and Europe, was described by Bala as a direct response to what he termed the 'political madness' of the recent Brexit referendum. Among the more controversial pieces was a crudely-drawn map of England and Wales, accompanied by an accusation that both nations were effectively 'self-harming' in a bid to 'take control of [their] own demise', along with other images in which Wales had become severed from the rest of Europe. This article will explore whether Bala's overt objections to Brexit have been seen more broadly across Welsh culture since June 2016 and how Welsh writers and artists might seek to resist the form of inner-emigration feared by Bala. Looking ahead, the article will consider whether, as Wales withdraws politically from the European Union, Welsh culture will adopt an inward gaze, or follow Bala's lead in rejecting the concept of self-isolation and using their creative work to reassert a new sense of Welsh identity in the wake of Brexit.